Strengthening Managerial Capacity in the Management of BOS Funds: Case Study From Educational Units in South Bolaang Mongondow Regency, Indonesia - Gobel, Cindra Dewi; Rahmisyari, R.; Arifin, T. (Golden Ratio of Data in Summary, 2026)
This study aims to: (a) analyze the strengthening of managerial capacity, and (b) identify inhibiting factors. This study employs a qualitative approach, involving the review, analysis, and interpretation of data. Data collection techniques include observation, interviews, and Documentation. And data analysis techniques: Data reduction, Data presentation, Triangulation, and Conclusions. Research results: (1) The education budget is allocated to strengthen management through training for school principals and treasurers, both offline and online, regarding regulatory changes. However, the 2024 BPK-RI audit found that in 81 educational units, managers did not participate in independent learning through internet-based resources, social media, and departmental discussions. Training covers planning, finance, supervision, evaluation, and reporting; treasurers assess reporting but rely on the stable BOS Reporting Information System. Social media facilitates access, while supervision and evaluation are carried out through financial planning, through learning, and regular meetings. (2) Lack of training reduces managerial skills, analysis, evaluation, and understanding of changing BOS regulations, increasing the risk of errors and decreasing performance. Treasurers, with the most considerable workload, require training ranging from transaction recording to technology application. Because regulations change annually, training is crucial. This exacerbates the burden, reduces effectiveness, transparency, and accountability, and undermines public trust.